MICROBIAL COMMUNITY PROFILES IN RIPENING OF BANANA BANANA (Musa acuminata AAA group) CAVENDISH WITH 1.25% CHITOSAN TREATMENT USING METAGENOMIC 16S RRNA ANALYSIS - Syam, Fidya
Banana ripening is a complex molecular process that produces visible changes in the texture, aroma, taste and nutritional content. In general, ripening process is controlled by genetic code, metabolic pathway and associated microbiome. This study aims to determine microbial community profile during the ripening process of bananas with chitosan 1.25% treatment. This research uses pulp and peel samples from the first and seventh days Cavendish banana cultivars (Musa acuminata cv. Cavendish AAA group) with chitosan 1.25% treatment and non-chitosan as control. Identification of specific microbiomes was carried out using 70% alcohol for endophytic microbes and distilled water for epiphytic microbes, so in total there were 16 types of samples without replicate. Postharvest analysis was done every 2 days for a week to measure changes in banana skin colour, starch content, weight loss percentage, pulp to peel (PTP) ratio and total suspended solid (TSS) ratio. Microbial community analysis was done using metagenomic 16s rRNA amplicon sequencing and bioinformatics anlayssis was done using software MOTHUR. Postharvest analysis showed that banana with chitosan treatment has experienced slower ripening process with lower index in banana skin colour chart, starch contet chart, weight loss percentage, PTP ratio, and TSS value compared by control banana. Microbes community profile showed that all sample was dominated by genus Alcaligene from family Burkhoideriaceae. OTU-based phylogenetic tree showed that chitosan treatment gives changes in microbes community structure that makes ripe and raw banana become clustered because of different type of treatment. Statistic analysis AMOVA (Analysis of Molecular Variance) showed that thereis no significant difference between all sample with p-value > 0.05.